Sequential doping strategy in rutile TiO2 nanorod for high performance photoanode - Lee, Sang Yeon; Lee, Young Jae; Yoo, Il Han; Kim, Hyeon Woo; Song, Hyejeong; Heo, Soo Won; Kalanur, Shankara S.; Mohapatra, Gourab; Rohma; Ko, Hyunseok; Seo, Hyungtak (Applied Surface Science, 2024)
Clean hydrogen production technologies are in high demand as an alternative to fossil fuels in order to achieve a carbon–neutral society. One promising approach is photoelectrochemical water splitting, which uses sunlight as an energy source to produce hydrogen. In this study, we propose a strategy for achieving highly efficient photoelectrochemical performance in TiO2 nanorods without the need for additional heterojunction or catalyst reactions. We introduce the plasma-assisted sequential doping process using H and F species to demonstrate highly efficient photoanode for water splitting. In the first stage, hydrogenated TiO2 generated oxygen vacancies and interstitial H in the TiO2 lattice structure, and in the second stage, fluorinated TiO2 exhibited a sequentially cured reaction of oxygen vacancy resulting in enhanced photoelectrochemical performance. Furthermore, theoretical simulations revealed that the sequential doping process induced a stabilized reaction in F compared to direct doping without H plasma doping. This sequential doping strategy can be applied to a wide range of materials and applications, not just to enhance photoelectrochemical devices.
Keywords: Doping process; Doping strategies; Hydrogen production technology; Performance; Photo-anodes; Photoelectrochemical performance; Plasma treatment; Rutile TiO 2; Sequential doping; Water splitting; Fluorine; Photoanode; Plasma treatment; Sequential doping; TiO2; Water splitting